Integrating Spiritual Values in Strengthening the Quality Culture in Islamic Senior High Schools: A Case Study at MAN IC Sorong - Hartinah; Putri Aulia Thamrin; Moch. Nur Syawalludin Nugroho (Journal of Pedagogy and Education Science, 2026)
The integration of spiritual values is a fundamental component of educational quality culture, serving as the foundation for character development, learning ethics, and the overall quality of educational services. Spiritual values such as sincerity, worship discipline, noble character, and responsibility not only strengthen institutional identity but also function as instruments for comprehensive quality improvement. This study aims to analyze how spiritual values are implemented to reinforce the quality culture at MAN IC, focusing on institutional vision, the effectiveness of spiritual development programs, and their impact on educational services and student character. Using a qualitative approach through observation and in-depth interviews with seven key respondents (school leaders, teachers, educational staff, dormitory supervisors, and students), this research identifies three main findings: (1)alignment of the institution’s spiritual vision with student diversity as the foundation of the school culture; (2)the effectiveness of dormitory-based programs (hidden curriculum) such as night prayers, halaqah, spiritual mentoring, Qur’an memorization, and the Monday–Thursday fasting routine, which foster a continuous 24-hour spiritual habit; and (3)the significant influence of spiritual values on more human-centered educational services and the enhancement of student character in terms of discipline, religiosity, and integrity. Overall, the integration of spiritual values has proven to be a central pillar in strengthening the quality culture at MAN IC, although further improvements are needed regarding implementation consistency, personalized guidance, and inter-unit collaboration to address diverse student backgrounds and digital-age challenges. These findings highlight the importance of systematic, adaptive, and sustainable spiritual development in improving educational quality.